Design and Development of a Geotagging and QR Code-Based Oil Palm Fertilization Tracking System Using Android Mobile Integration and LoRa SX1278 - Mohammad Farodis Azhari; Ratu Mutiara Siregar; Andi Prayogi (Universitas Malikussaleh, 2026)
This research proposes the development of an Internet of Things (IoT) monitoring system for tracking and verifying palm oil fertilization based on Geotagging and QR Code to overcome challenges in manual fertilization supervision, such as location accuracy, dose precision, and transmission vulnerabilities in remote areas. The system ensures compliance with field standard operating procedures (SOP) through a dual-validation mechanism: spatial coordinate recording via geotagging for location audit trails, and QR Code scanning for fertilizer identity verification. The hardware system architecture integrates a ESP32 microcontroller, a NEO-6M GPS module, and a LoRa Ra-02 SX1278 (433 MHz) transceiver mounted directly on the wheelbarrow. Field workers utilize a Flutter-based mobile Android application to scan the fertilizer labels, which wirelessly forwards data via a Bluetooth Low Energy (BLE 4.2) link to the ESP32. Field integration trials conducted at the ITSI Campus estate demonstrated that the wheelbarrow unit successfully captures high-precision coordinates by locking onto 7 active satellites under dense palm oil canopies with a 3-second refresh rate. Out of 20 live fertilization check-ins executed during the field-testing sessions, the system successfully logged 14 valid transactions and flagged 6 operational deviations, achieving a definitive 70.0% geotagging compliance rate. Furthermore, the offline-first local cache layer guaranteed zero data loss inside cellular blank spots by securely holding transaction logs before automatically synchronizing them to the Firebase Realtime Database. This architecture effectively mitigates the telecommunication infrastructure barrier in remote plantation sectors while generating verifiable, tamper-proof digital audit trails.